2008
DOI: 10.1161/circulationaha.107.719807
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Sarcoplasmic Endoplasmic Reticulum Ca 2+ -ATPase and μ-Calpain Activity Are Altered in Type 2 Diabetes Mellitus and Restored by Rosiglitazone

Abstract: Background-Platelets from patients with type 2 diabetes mellitus display hyperaggregability and increased thrombogenic potential. Methods and Results-In platelets from patients with type 2 diabetes mellitus, we found enhanced tyrosine nitration and inactivation of the sarcoplasmic endoplasmic reticulum Ca 2ϩ -ATPase (SERCA-2), elevated platelet [Ca 2ϩ ] i , and activation of -calpain. The tyrosine nitration of SERCA-2 and the activation of -calpain in vitro in platelets from healthy volunteers could be evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 41 publications
4
69
0
3
Order By: Relevance
“…Because platelet agonists alone are poor activators of the protease, calpains were activated via the Ca 2ϩ -sensing receptor by increasing the extracellular concentration of Ca 2ϩ as described previously 12 or using the combination of Ca 2ϩ and ionomycin. The 2 approaches were also used to differentiate between -and m-calpain activation, both of which are expressed in platelets.…”
Section: Proteomic Analysis Of Platelets From Patients With and Withomentioning
confidence: 99%
See 2 more Smart Citations
“…Because platelet agonists alone are poor activators of the protease, calpains were activated via the Ca 2ϩ -sensing receptor by increasing the extracellular concentration of Ca 2ϩ as described previously 12 or using the combination of Ca 2ϩ and ionomycin. The 2 approaches were also used to differentiate between -and m-calpain activation, both of which are expressed in platelets.…”
Section: Proteomic Analysis Of Platelets From Patients With and Withomentioning
confidence: 99%
“…This leads to the limited proteolysis of target proteins without eliciting full-blown platelet activation. 12 Several platelet proteins are known to be calpain substrates, including spectrin, adducin, talin, CD31, the myosin light-chain kinase, and N-ethylmaleimide-sensitivefactor attachment receptor (SNARE) proteins such as SNAP-23 and vesicle-associated membrane protein 3 (VAMP-3). 13 However, the spectrum of proteins that serve as pathophysiologically relevant targets of calpain in diabetic humans and their eventual role in the accelerated development of cardiovascular disease is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a related development, Randriamboavonjy et al, (2008) also demonstrated that treatment of megakaryocytes and platelets with rosiglitazone upregulates SERCA2b.…”
Section: Rosiglitazone and Calcium Homeostasismentioning
confidence: 89%
“…La sobreexpresión de SERCA revirtió el efecto del ácido palmítico sobre la señaliza-ción de la insulina, indicando que la reducción de su expresión y de su actividad sería la causa de que el ácido palmítico induzca un estado de resistencia en las células endoteliales 71 . El tratamiento de las personas diabéticas con rosiglitazona, un fármaco antidiabético, incrementó la expresión de SERCA, restaurando la reducción de la expresión de la bomba observada en pacientes diabéticos con hiperglucemia alterada 72 . El empleo de la chaperona química TUDCA restaura la expresión y la actividad de la bomba SERCA en ratones obesos (ob/ ob) 73 .…”
Section: Papel De Los áCidos Grasos En El Estrés Del Retículo Endopláunclassified